Working across boundaries in regional place-based food systems: Triggering transformation in a time of crisis. (November 2022) - Lever, John; Blake, Megan; Newton, Dillon; Downing, Gareth
Abstract: Drawing on research exploring food system change in a region in the North of England during the Covid-19 health pandemic, in this paper we explore how a "managerial" approach to food system governance and provisioning embedded in national food systems and international supply chains was suddenly supplanted by a more "open" approach. By enabling understanding of how food system change unfolded as a diverse range of hidden practices unexpectedly became visible, it contributes to food systems thinking through the development of a regional place-based perspective. We use this approach to understand the outcome of these processes and to investigate how embedding change across administrative and geographical boundaries can enable food system transformation to improve food security for future generations. Graphical abstract: Unlabelled Image Highlights: When places change suddenly the potential for transformation becomes visible. Strengthening geographical connections can further a sense of place. Working across food system boundaries can improve food security for future generations.